Comparative safety and efficacy of antithrombotics in the management of venous thromboembolism after knee or hip replacement surgery: focus on rivaroxaban - Kwong LM (Dove Medical Press, 2013)
Louis M KwongDepartment of Orthopedic Surgery, Harbor-UCLA Medical Center, Torrance, CA, USAAbstract: Routine thromboprophylaxis represents the current standard of care in the management of patients following total hip or knee replacement. Legacy agents used to address the issue of risk of venous thromboembolism present barriers to use, either by the need for monitoring and dose adjustment (warfarin) or the need for injection (low molecular weight heparins and fondaparinux), or pose a risk of upper gastrointestinal bleeding (acetylsalicylic acid and all antithrombotic agents). The introduction of new pharmacologic agents in recent years has sought to address the issues of not only efficacy, but also safety, ease of use, and patient compliance. New orally administered agents, ie, apixaban, dabigatran, and rivaroxaban, have demonstrated various degrees of efficacy over enoxaparin while preserving safety. Indirect comparisons of the relative efficacies of apixaban, dabigatran, and rivaroxaban have shown rivaroxaban to be more efficacious than dabigatran and apixaban in reducing symptomatic and total venous thromboembolism following total hip or knee replacement surgery. A pooled analysis of the four RECORD (Regulation of Coagulation in Orthopedic Surgery to Prevent deep vein thrombosis and pulmonary embolism) trials (two in total hip replacement and two in total knee replacement) demonstrated rivaroxaban to be the first and only antithrombotic agent ever to demonstrate superiority in reducing symptomatic venous thromboembolism and all-cause mortality compared with another antithrombotic agent (enoxaparin). New oral antithrombotic agents have demonstrated efficacy in prophylaxis against venous thromboembolism following total hip or knee replacement surgery while preserving safety, with increased ease of administration of thromboprophylaxis for both the patient and the physician, which may contribute to improved compliance.Keywords: thromboprophylaxis, venous thromboembolism, rivaroxaban, total hip replacement, total knee replacement